Recent advances of metal vacancies in energy and environmental catalysis: Synthesis, characterization, and roles - Long Sun; Shunzheng Zhao; Sirui Gao; Ronghui Zhu; Yiran Tan; Xiaolong Tang; Honghong Yi (Green Energy & Environment)
With the ongoing depletion of fossil fuels, energy and environmental issues have become increasingly critical, necessitating the search for effective solutions. Catalysis, being one of the hallmarks of modern industry, offers a promising avenue for researchers. However, the question of how to significantly enhance the performance of catalysts has gradually drawn the attention of scholars. Defect engineering, a commonly employed and effective approach to improve catalyst activity, has become a significant research focus in the catalysis field in recent years. Non-metal vacancies have received extensive attention due to their simple form. Consequently, exploration of metal vacancies has remained stagnant for a considerable period, resulting in a scarcity of comprehensive reviews on this topic. Therefore, based on the latest research findings, this paper summarizes and consolidates the construction strategies for metal vacancies, characterization techniques, and their roles in typical energy and environmental catalytic reactions. Additionally, it outlines potential challenges in the future, aiming to provide valuable references for researchers interested in investigating metal vacancies.